2013
DOI: 10.1093/humrep/det093
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin promotes development and function of macaque primary follicles during encapsulated three-dimensional culture

Abstract: This work was supported by The Oncofertility Consortium (NIH U54 RR024347-HD058294, PL1-EB008542), NIH U54-HD18185 (Eunice Kennedy Shriver Specialized Cooperative Centers Program in Reproduction and Infertility Research), NIH ORWH/NICHD 2K12HD043488 (BIRCWH), Oregon National Primate Research Center 8P51OD011092. There are no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 39 publications
(80 reference statements)
5
132
0
4
Order By: Relevance
“…Notably, in vitro-developed macaque follicles produced AMH with expression patterns similar to those observed in women by immunohistochemistry [11]. Media concentrations of AMH protein were detectable during the preantral stage and peaked after antrum formation [10]. The data also indicated that, although the diameters were similar at onset of culture, macaque preantral follicles differ in their ability to produce AMH.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Notably, in vitro-developed macaque follicles produced AMH with expression patterns similar to those observed in women by immunohistochemistry [11]. Media concentrations of AMH protein were detectable during the preantral stage and peaked after antrum formation [10]. The data also indicated that, although the diameters were similar at onset of culture, macaque preantral follicles differ in their ability to produce AMH.…”
Section: Introductionsupporting
confidence: 57%
“…The data also indicated that, although the diameters were similar at onset of culture, macaque preantral follicles differ in their ability to produce AMH. Media AMH concentrations correlate positively with follicle growth rates during monkey follicle culture [10]. Thus, macaque follicles grown in vitro may mimic those developed in vivo in terms of AMH production.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Follicle culture at different stages of development has been used to study diverse biological processes (folliculogenesis, steroidogenesis, and oocyte maturation) in various species, such as goat [9,10], mouse [11][12][13], rat [14], sheep [15,16], dog [17][18][19], and monkey [20][21][22][23]. Regarding the domestic cat, efforts to date have focused on oocytes [7,[24][25][26][27][28][29][30] or preantral follicle cultures [19,31].…”
Section: Introductionmentioning
confidence: 99%